Evaluation of an External Quality Assessment Program for HIV Testing in Tigray North Ethiopia 2016 - Gebrehiwet Tesfahuneygn; Gebremichael Gebreegziabher (Journal of Clinical Research In HIV AIDS And Prevention, 2017)
Background: Point-of-care diagnostic tests (POCTs) are increasingly used in both developing and developed countries. They allow same day testing and treatment at remote locations where no laboratory support is available. Quality control measures, which are routinely used in laboratories, have not been widely implemented for POCTs. This aimed to assess the integrity of the entire laboratory testing process, and aims to educate and improve performance in quality of HIV rapid testing. Methods: A health facility based cross section study was conducted from April to June 2016.Randomly selected health facilities were participated in the external quality assessment. Onsite evaluation and panel test were used to collect data using structured checklists and formats. Data was entered and analyzed using SPSS version 16. Results: Between April to June 2016, a total of 60 health facilities (145 testing points) from governmental health facilities (hospitals and health centers) were participated in the study. Among the participated testing points 41% have no designated area, 40% have no clean water for hand washing and 51% have no national test algorithm. The average performance of testing points was varies from 89.6% to 99.1% (Laboratory 99.1%, ANC 90.4%, TB clinic 91.4% and VCT 89.6%). In a multivariable logistic regression model, didn’t follow national testing algorithm to report client test results have statistical significance. Conclusions: High quality test results underpin accurate diagnosis and appropriate treatment for patients. But in the study area the score of proficiency testing result and coverage of training is slightly low comparing to other findings. Therefore following national testing algorithm to report client test results, training and monitoring are critical points to improve the proficiency testing score of testing points.
Keywords: HIV Testing